NICOSULFURON PHYTOTOXICITY ON VEGETATIVE PARAMETERS AND YIELD COMPONENTS OF BEAN (PHASEOLUS VULGARIS L.) - Lazarević, Jovan; Laloš, Bojan; Pavlović, Miloš (Acta herbologica, 2023)
Nicosulfuron (C15H18N6O6S) is a selective, translocating herbicide from the chemical group of sulfonylureas, which represent one of the most commonly applied groups of herbicides, especially in field plants. The aim of the work was to examine the effect of simulated drift of nicosulfuron on the bean crop, and that effect was monitored through vegetative parameters and yield components. The experiment was carried out in 2020 on the experimental field of the Research and Development Institute "Tamiš", in Pančevo (Vojvodina, Serbia). Beans (Phaseolus vulgaris L.), Galeb variety, were used for testing. Five treatments (five different concentration of nicosulfuron) were included in this trial, namely: 10%, 5%, 2,5%, 1,25%, 0,62% of the recommended amount of application and a control treatment (without the application of the active substance). The obtained results showed that there were no significant differences in the height of the bean plants between the treatments, but the treatment with the lowest concentration of nicosulfuron (0.62%) had a hormesis effect. It was observed that with an increase in the amount of nicosulfuron applied, the number of side branches and grain yield per m2 decreased, but the differences obtained between the treatments were not statistically significant. Significant differences compared to the control were recorded only in the number of pods, when nicosulfuron was applied in a concentration of 10% of the recommended dose. The obtained results are significant from the point of view of practical agricultural production because the drift of herbicide working liquid is a frequent phenomenon in practice, so it is important to know the potential unwanted effects on the neighboring, non-target crop.